Short food supply chains as a meachanism for sustainable development - Lucian Tanasă; Codrin Dinu Vasiliu; Ioan Sebastian Brumă; Sebastian Doboş (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
At present, gastronomy is becoming an increasingly stronger motivation and focus of interest in economics, especially in fields related to tourism. At the same time, gastronomic tourism represents one of the most important business opportunities, allowing direct contact between food sector producers and tourists. Moreover, food related tourism is a key factor of success for local food fests and food markets based in touristic destinations. Thus, food related tourism represents an important incentive for the development of short food supply chains, resulting in the cooperation between local producers and tourism operators. In satisfying the demand of tourists interested especially in gastronomical aspects, local economic operators, whether small food sector producers or accommodation unit owners, are compelled to cooperate and complement each other. The present study aims to discuss this particular economic mechanism specific to the Târgu Neamðt touristic area, by taking into consideration both its strengths (especially regional cultural, historical heritage and natural habitat) as well as its weaknesses, represented by the local producers' lack of access to an adequate market, which is a key factor in ensuring long term regional proper development opportunities. Our conclusion is that, at least one potential solution to achieving sustainable development in the Târgu Neamðt region, is to encourage the establishment of long lasting mutually beneficial partnerships between local food sector producers and tourism sector operators.
Keywords: Q13; Q11; O13; O16; O18; M31; L83; 330; short food supply chains; gastronomic tourism; rural tourism; Tæargu Neamðt touristic area; local producers; local sustainable development